Fear of Success with Job Satisfaction on Bank Employees - Tadoe, Sandly Marthyn; Keraf, M. K. P. Abdi; Pello, Shela Ch (Journal of Health and Behavioral Science, 2023)
Fear of success is a form of anxiety caused by a desire to achieve success, but worrying about the consequences of their success. The tendency fear of success can have a negative impact on individual employees, jobs, and companies. The research hypothesis is that there a relationship between loss of femininity, loss of social self-esteem, social rejection with job satisfaction on female employees at Bank NTT. The research participants were 107 female employees at Bank NTT using purposive sampling with data analysis using Spearman Rank correlation. The results say there is no relationship between loss of femininity and job satisfaction because the value of sig. 0.080 and correlation value -0.170, while there is a relationship between loss of social self-esteem and job satisfaction, because the value of sig. 0.000 and correlation value -0.350, and there is a relationship between social rejection and job satisfaction, because the value of sig. 0.000 and the correlation value -0.466.